An evaluation of the clinical and cost-effectiveness of alternative care locations for critically ill adult patients with acute traumatic brain injury. (3rd July 2016) - Grieve, R.; Sadique, Z.; Gomes, M.; Smith, M.; Lecky, F. E.; Hutchinson, P. J. A.; Menon, D. K.; Rowan, K. M.; Harrison, D. A.; ,
Abstract: Background: For critically ill adult patients with acute traumatic brain injury (TBI), we assessed the clinical and cost-effectiveness of: (a) Management in dedicated neurocritical care units versus combined neuro/general critical care units within neuroscience centres. (b) 'Early' transfer to a neuroscience centre versus 'no or late' transfer for those who present at a non-neuroscience centre. Methods: The Risk Adjustment In Neurocritical care (RAIN) Study included prospective admissions following acute TBI to 67 UK adult critical care units during 2009–11. Data were collected on baseline case-mix, mortality, resource use, and at six months, Glasgow Outcome Scale Extended (GOSE), and quality of life (QOL) (EuroQol 5D-3L). We report incremental effectiveness, costs and cost per Quality-Adjusted Life Year (QALY) of the alternative care locations, adjusting for baseline differences with validated risk prediction models. We tested the robustness of results in sensitivity analyses. Findings: Dedicated neurocritical care unit patients ( N  = 1324) had similar six-month mortality, higher QOL (mean gain 0.048, 95% CI −0.002 to 0.099) and increased average costs compared with those managed in combined neuro/general units ( N  = 1341), with a lifetime cost per QALY gained of £14, 000. 'Early' transfer to a neuroscience centre ( N  = 584) was associated with lower mortality (odds ratio 0.52, 0.34–0.80), higher QOL for survivors (mean gain 0.13, 0.032–0.225), but positive incremental costs (£15, 001, £11, 123 to £18, 880) compared with 'late or no transfer' ( N  = 263). The lifetime cost per QALY gained for 'early' transfer was £11, 000. Conclusions: For critically ill adult patients with acute TBI, within neuroscience centres management in dedicated neurocritical care units versus combined neuro/general units led to improved QoL and higher costs, on average, but these differences were not statistically significant. This study finds that 'early' transfer to a neuroscience centre is associated with reduced mortality, improvement in QOL and is cost-effective.